2005
DOI: 10.1582/leukos.2004.01.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Task lighting effects on office worker satisfaction and performance, and energy efficiency

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Task ambient (TA) lighting can reduce energy consumption by combining a low uniform lighting system and a local lighting system instead of conventional uniform lighting systems while maintaining the light levels around working spaces. Previous studies 1,2 have revealed that TA lighting is also effective in increasing worker satisfaction and productivity. However, evaluations in previous studies were based mainly on questionnaires (subjective evaluation) and/or simulated office tasks, which might be greatly affected by a learning effect.…”
Section: Introductionmentioning
confidence: 94%
“…Task ambient (TA) lighting can reduce energy consumption by combining a low uniform lighting system and a local lighting system instead of conventional uniform lighting systems while maintaining the light levels around working spaces. Previous studies 1,2 have revealed that TA lighting is also effective in increasing worker satisfaction and productivity. However, evaluations in previous studies were based mainly on questionnaires (subjective evaluation) and/or simulated office tasks, which might be greatly affected by a learning effect.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, the user might hunch or move closer to the task while trying to read text that is affected by glare, reflection or poor contrast (Joines et al, 2015). Proper task lighting can help mitigate these negative effects on the posture, eye strain and visual comfort of the user (Newsham et al, 2005;Joines et al, 2015). Furthermore, studies have linked exposure to blue light during night to disruption in the circadian rhythm and increased risk of breast and colorectal cancer (Stevens, 2009;James et al, 2016).…”
Section: Visual Conditionsmentioning
confidence: 99%
“…The relationship between task lighting on occupant's mood, satisfaction, and performance and its correlation to energy savings, using as reference illuminance values, as suggested by Green Star (Green Building Council of Australia-GBCA) and Illuminating Engineering Society of North America (IESNA) allowed for concluding that there was no direct association among these variables [33]. On the contrary, when comparing the actual energy intensity use to the baseline model of seven offices or libraries buildings, and four multi-family residential buildings certified by the green building certification tool LEED (Leadership in Energy and Environmental Design), it was possible to conclude that almost all of the buildings had savings of over 40%, when compared to the design model projections, but there was no clear relationship between occupant satisfaction in comfort temperature and the building energy intensity [34].…”
Section: Sustainability Toolsmentioning
confidence: 99%